Physics and chemistry of the deep Earth - Karato, Shun'ichirō, 1949- (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley - Blackwell, 2013)
Though the deep interior of the Earth (and other terrestrial planets) is inaccessible to humans, we are able to combine observational, experimental and computational (theoretical) studies to begin to understand the role of the deep Earth in the dynamics and evolution of the planet. This book brings together a series of reviews of key areas in this important and vibrant field of studies. A range of material properties, including phase transformations and rheological properties, influences the way in which material is circulated within the planet. This circulation re-distributes key mat.
pt. 1. Materials' properties -- pt. 2. Compositional models -- pt. 3. Geophysical observations and models of material circulation.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Geophysics; Geochemistry; Earth -- Core; Geochemistry; Geophysics; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Core of the Earth; Geochemistry; Geophysics; Earth (Planet) -- Core; Electronic books